The plurinational state in international law - Tudela Chopitea, Alejandro (2022)
This essay succinctly traces the path of modern state organization from the Nation-State from the Treaties of Westphalia (1648) to the Plurinational State with indigenist roots that appeared in South America in the first decade of the 21st century. Being its purpose, essentially, this last form of State, the main constitutional guidelines of the same content are presented in the Fundamental Charters of Bolivia and Ecuador, countries that adhere to this model, as well as the proposal of the Constituent Convention of Chile of very similar orientation that will be submitted in a few months to popular consultation.